2006
DOI: 10.1002/nau.20360
|View full text |Cite
|
Sign up to set email alerts
|

Management of refractory urinary urge incontinence following urogynecological surgery with sacral neuromodulation

Abstract: Aims: We sought to explore our patient outcomes utilizing sacral neuromodulation in the management of refractory urinary urge incontinence following urogynecological surgical procedures. Methods: A total of 25 women with urinary urge incontinence following urogynecological surgery were selected for SNS therapy and retrospectively analyzed. All patients completed a comprehensive urological evaluation. Clinical data was recorded to determine outcomes and identify parameters that would be predictive of response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 42 publications
1
23
2
Order By: Relevance
“…From an initial 456 publications identified by the literature search, 73 articles were included, of which 8 are randomized controlled trials (RCTs) [7][8][9][10][11][12][13][14], 7 are comparative studies [15][16][17][18][19][20][21], 46 are prospective and 10 are retrospective case series [68][69][70][71][72][73][74][75][76][77], and 2 combine prospective and retrospective case series in the same article [78,79]. The screening process is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From an initial 456 publications identified by the literature search, 73 articles were included, of which 8 are randomized controlled trials (RCTs) [7][8][9][10][11][12][13][14], 7 are comparative studies [15][16][17][18][19][20][21], 46 are prospective and 10 are retrospective case series [68][69][70][71][72][73][74][75][76][77], and 2 combine prospective and retrospective case series in the same article [78,79]. The screening process is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between the years of 1993 and 2009 and include 5 RCTs [9-11, 13, 14], 23 prospective [24, 25, 27-30, 32, 34, 35, 37, 41, 42, 44, 46, 48, 56, 58, 61-66] and 10 retrospective case series [68][69][70][71][72][73][74][75][76][77], and 2 combined prospective/retrospective case series [78,79]. UUI was the most common indication studied: 34 studies included patients with UUI symptoms and 11 studies investigated this population exclusively.…”
Section: Implanted Sacral Nerve Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its proven effectiveness, the search to expand the indications for SNM in complex patient populations is inevitable. Two studies have shown that SNM is effective in the treatment of de novo or worsening OAB after SUI surgery [13,14]. The study by Sherman et al [13] noted that 26% of patients had undergone a sling release procedure and found that this parameter was not predictive of response to SNM.…”
Section: Discussionmentioning
confidence: 99%